Cultural Competency Training in a Global Society - Dana, Richard H. (Springer, 2017)
Cultural competence is more than an admirable goal: it is an essential skill set for mental health professionals working in a diverse global society marked by crisis and trauma. It is essential for clinicians to understand the intricate mix of history and self-concept, identity and tradition that are central not only for ameliorating psychological problems but to foster psychological health and well-being. As the definition of culture takes on broader meanings-at once embracing multiple identities and increasing globalization- Cultural Competency Training in a Global Society brings a vital perspective and practical understanding to clinical, counseling, and school psychologists, as well as to graduate students entering these fields. By describing a comprehensive training model for professional education and practice in the United States with ethnic minority groups, indigenous populations, immigrants, and refugees, this book has relevance for other multicultural societies because the implications are multidisciplinary in focus and potentially international in scope. The existing and emergent global multicultural populations described in this book represent the neglected human faces of economic globalization. Among the topics covered: Requirements for professional training in cultural competency. Research basis for cultural competency training. International resources and their usage in training and practice. Multicultural assessment in the service of intervention. Evaluating cultural competency training.